Development of Evolution Theory in Modern Linguistics - Iskakova Н.С.; Islam А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
This article is devoted to the problem of studying evaluation as a linguistic phenomenon. In general, the evaluation as a universal phenomenon has for a long time been attracting the attention of psychologists, philosophers, logicians, and at the present stage has become particularly relevant in linguistic descriptions. The article discusses the basic approaches such as logical- philosophical, functionalsemantic, communicative-pragmatic and cognitive to the study of evaluation theory and various stages of its development. The scientific literature review from ancient times to the present is provided, based on the different points of view of evaluation as a whole. The main issues related to the study of evaluation theory in linguistic studies are outlined and the evaluation structure that varies depending on the composition and the number of elements allocated in the structure of evaluation are also reviewed.